2013
DOI: 10.1128/aem.02044-13
|View full text |Cite
|
Sign up to set email alerts
|

The Virulence of Salmonella enterica Serovar Typhimurium in the Insect Model Galleria mellonella Is Impaired by Mutations in RNase E and RNase III

Abstract: Salmonella enterica serovar Typhimurium is a Gram-negative bacterium able to invade and replicate inside eukaryotic cells. To cope with the host defense mechanisms, the bacterium has to rapidly remodel its transcriptional status. Regulatory RNAs and ribonucleases are the factors that ultimately control the fate of mRNAs and final protein levels in the cell. There is growing evidence of the direct involvement of these factors in bacterial pathogenicity. In this report, we validate the use of a Galleria mellonel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 81 publications
5
61
0
1
Order By: Relevance
“…Altogether, we detected a total of 2,557 mRNAs cleaved by RNase E, with a different number of cleavage sites per transcript (Figure 2B); these represent 78% of 3,286 Salmonella mRNAs that are well expressed (RPKM > 10, Table S2) in the early stationary phase. Notably, the assay captured many essential genes and virulence genes required for intracellular growth (Table S3), which provide insights into the processing of transcripts from indispensable genes and the roles of RNase E in Salmonella pathogenesis (Viegas et al., 2013), respectively. Longer transcripts generally tend to contain a higher number of cleavage sites (Figures S1D and S1E).…”
Section: Resultsmentioning
confidence: 99%
“…Altogether, we detected a total of 2,557 mRNAs cleaved by RNase E, with a different number of cleavage sites per transcript (Figure 2B); these represent 78% of 3,286 Salmonella mRNAs that are well expressed (RPKM > 10, Table S2) in the early stationary phase. Notably, the assay captured many essential genes and virulence genes required for intracellular growth (Table S3), which provide insights into the processing of transcripts from indispensable genes and the roles of RNase E in Salmonella pathogenesis (Viegas et al., 2013), respectively. Longer transcripts generally tend to contain a higher number of cleavage sites (Figures S1D and S1E).…”
Section: Resultsmentioning
confidence: 99%
“…Evidence accumulated in recent years has demonstrated that G. mellonella larvae can be used as an attractive alternative model to identify the virulence of various pathogens (42,(47)(48)(49)(50). In this study, we investigated the extent to which the virulence factors required for pathogenesis in both ducklings and G. mellonella larvae overlap.…”
Section: Discussionmentioning
confidence: 99%
“…Larvae of the wax moth Galleria mellonella are an abundantly used in vivo infection model, including those with enteric pathogens such as enteropathogenic E. coli (EPEC) and Salmonella (Leuko and Raivio, 2012;Viegas et al, 2013). It is particularly suited to study interactions between pathogens and phagocytic cells in a living organism (Harding et al, 2012).…”
Section: Mam Is Required For S Sonnei Pathogenesis and Interaction Wmentioning
confidence: 99%
“…Therefore, other animal models such as the murine lung and rabbit ligated ileal loop models have been developed for defining some of the immune and inflammatory components of the disease (Philpott et al, 2000). Recently, the great moth, G. mellonella, has gained popularity as a model for assessing virulence and a number of pathogens have been studied using this model, including enteropathogenic E. coli (EPEC), Salmonella typhimurium and Listeria monocytogenes (Leuko and Raivio, 2012;Harding et al, 2013;Viegas et al, 2013). To our knowledge, this study is the first to report the use of this model for assessing virulence of Shigella.…”
Section: G Mellonella Larvae Infection Modelmentioning
confidence: 99%